2017
DOI: 10.1007/s00408-017-0022-5
|View full text |Cite
|
Sign up to set email alerts
|

Lung Clearance Index (LCI) is Stable in Most Primary Ciliary Dyskinesia (PCD) Patients Managed in a Specialist Centre: a Pilot Study

Abstract: Primary ciliary dyskinesia is a condition in which abnormal cilia structure or function leads to reduced mucociliary clearance and obstructive lung disease. Twenty-nine patients had lung clearance index (LCI) measured in 2009 and we attempted to perform a 5-year follow-up. Only 12 patients could be re-recruited, but in this small group LCI was stable over the 5 years, which confirms previous data showing that spirometry is also stable in these patients over the medium term. The two patients with the highest LC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
(14 reference statements)
1
3
1
Order By: Relevance
“…Contrary to our finding, a pilot study by Irving et al [29], which measured the LCI twice with 5-year interval in 12 PCD patients, found no significant overall change in the LCI. This difference might be because Irving's study group was simply too small to find the rather small increase in LCI, which we demonstrated; another tracer gas was used (sulphur hexafluoride); the patient cohorts might be different with respect to age, infection status, or other disease characteristics; or management practices might be different.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our finding, a pilot study by Irving et al [29], which measured the LCI twice with 5-year interval in 12 PCD patients, found no significant overall change in the LCI. This difference might be because Irving's study group was simply too small to find the rather small increase in LCI, which we demonstrated; another tracer gas was used (sulphur hexafluoride); the patient cohorts might be different with respect to age, infection status, or other disease characteristics; or management practices might be different.…”
Section: Discussioncontrasting
confidence: 99%
“…They found no trend in LCI or FEV 1 over an average of 1 year's observation. Similar results have been reported in a small study ( n = 12) by Irving et al who compared baseline LCI values to values obtained at a five‐year follow‐up and found an overall nonsignificant change in LCI (Irving et al, 2017). To the contrary, Kobbernagel et al found a minimal, but significant worsening of LCI during a one‐year observation period, while FEV 1 remained unchanged (Kobbernagel et al, 2019).…”
Section: Pulmonary Function—evolution From Infancy To Older Age Groupssupporting
confidence: 87%
“…FEV 1 was compared to MBW-derived LCI in eight studies, also with contradictory results. Two studies reported no association [ 41 , 44 ], while the other six [ 12 , 35 , 42 , 43 , 46 , 49 ] found correlations between some parameters. Both B oon et al [ 12 ] and K obbernagel et al [ 46 ] found a significant negative correlation between LCI, FEV 1 and FEV 1 /FVC ratio z-scores, while I rving et al [ 43 ] only found a correlation between LCI and forced expiratory flow at 25–75% of FVC (FEF 25–75 ) z-scores.…”
Section: Resultsmentioning
confidence: 99%